The disaster communication system in the city of Medan - Syafrizaldi, Syafrizaldi; Kholil, Syukur; Samosir, Hasrat Efendi; Sikumbang, Ahmad Tamrin (Jurnal Studi Komunikasi, 2022)
This study aims to analyse the communication system carried out in disaster management in Medan City, analyse the communication system carried out by the Medan City Regional Disaster Management Agency (BPBD) in tackling disasters in Medan City according to Islamic communication principles, analyse the BPBD communication system model in tackling disasters in Medan City, and analyse the communication barriers faced by the Regional Disaster Management Agency (BPBD) in tackling disasters in the city of Medan. This study uses several theories, namely communication formulas according to Harold Lasswell, dependency theory (dependency theory) and innovation diffusion theory, to describe the basic concepts and discuss research findings. This research is a research with a qualitative approach and uses a descriptive method after doing data collection by using interviews and documentation. The data analysis results show that the Regional Disaster Management Agency (BPBD) of Medan City applies a communication system according to the communication formula according to Harold D Lasswell.